Prevalence of anxiety and depression symptoms in a sample of outpatients with ATTR cardiac amyloidosis - Smorti, Martina; Ponti, Lucia; Soffio, Francesco; Argirò, Alessia; Perfetto, Federico; Zampieri, Mattia; Mazzoni, Carlotta; Tomberli, Alessia; Allinovi, Marco; Di Mario, Carlo; Olivotto, Iacopo; Cappelli, Francesco (Frontiers in Psychology, 2023)
Patients with ATTR cardiac amyloidosis (ATTR-CA) face rare disease that could negatively influence psychological well-being with consequences on the course of the disease and quality of life. However, to date, no study analyzed the prevalence of anxiety and depression in patients with ATTR-CA and which clinical and sociodemographic characteristics are linked with these psychopathological conditions. A total of 109 consecutive patients (83% males) aged 62 to 90 years with ATTR-CA were recruited. The level of anxiety and depression was measured using the Italian version of the Hospital Anxiety and Depression Scale (HADS). Sociodemographic and clinic characteristics were registered. Almost half of patients (49%) reported a clinical level of depression or anxiety, or both. Results showed that older patients, especially females, with more advanced disease could be more at risk to develop an anxious disorder. Furthermore, being a woman, and presenting with a greater severity of symptoms, would appear to be a risk factor for developing a depressive disorder. Overall, these results highlighted the high presence of anxiety and depression in ATTR-CA patients, suggesting to physicians to pay attention to the psychological well-being of ATTR-CA patients. In fact, a psychological support for patients with high level of psychopathological disease could reduce disease burden and improve quality of life in ATTR-CA population.